Development of Expertise in Spanish Elite Basketball Coaches.(El desarrollo de la pericia en los entrenadores españoles expertos en baloncesto.) - Sergio Jiménez Sáiz; Alberto Lorenzo Calvo; Sergio J. Ibáñez Godoy (Ramón Cantó Alcaraz, 2009)
Abstract The present study was designed to address two issues: first, to identify the different development stages that eight expert Spanish basketball coaches go through; and second, to determine the possible factors that have contributed to the formative or training, process of the expert coach. Qualitative data were gathered in semi-structured interviews. The coaches worked with the men's first Spanish Basketball League ("ACB" league) or the Spanish national selection. Our findings reveal four stages in the coach development process. These stages were the consequence mainly of a gradual progression in thinking and reflective practice that enabled the coach to optimize the necessary skills for high performance. In addition, all the coaches interviewed reflected an intense dedication and commitment over many years to their work, as well as an ongoing quest for improvement. Resumen El presente estudio fue diseñado para hacer frente a dos cuestiones: en primer lugar, identificar las diferentes etapas formativas de ocho entrenadores expertos en baloncesto, y en segundo lugar, determinar los posibles factores que han contribuido a la formación del entrenador experto. La metodología utilizada es la cualitativa y la técnica de recogida de datos fue la entrevista semiestructurada. Los entrenadores entrevistados pertenecían a la liga ACB o a la selección nacional española. Nuestros resultados ponen de manifiesto cuatro etapas en el desarrollo de su pericia. Estas etapas son consecuencia principalmente de un desarrollo de su conocimiento, así como de una profunda reflexión práctica que permitió al entrenador optimizar las habilidades necesarias para trabajar en el alto rendimiento. Además, todos los entrenadores reflejan una intensa dedicación y compromiso durante muchos años hacia su trabajo, así como una búsqueda constante por mejorar.